2009
DOI: 10.1001/archinternmed.2008.578
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Food, Calcium, and Risk of Cancer in the NIH-AARP Diet and Health Study

Abstract: Background Dairy food and calcium have been hypothesized to play roles that differ among individual cancer sites, but the evidence has been limited and inconsistent. Moreover, the effect of dairy food and calcium on cancer in total is unclear. Methods Dairy food and calcium in relation to total cancer as well as cancer at individual sites were examined in the NIH-AARP Diet and Health Study. Intakes of dairy food and calcium from foods and supplements were assessed with a food frequency questionnaire. Inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
160
3
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 51 publications
14
160
3
5
Order By: Relevance
“…Interestingly, high calcium contents of experimental diets have been shown to reduce CRC risk associated with (processed) red meat intake both in animals (Sesink et al, 2001) and in humans , probably through interference with the effects of heme. In spite of the presence of inflammatory Neu5Gc, the significantly higher calcium levels in processed dairy products (»500 mg/100g) compared to processed red meat (»10 mg/ 100 g) (NUBEL, 2013) may thus account for the protective effects of dairy foods as reported earlier (Park et al, 2009;Pala et al, 2011). Anyway, the near absence of Neu5Gc in poultry and fish could provide an explanation for the "white meat controversy" and its importance justifies further research efforts.…”
Section: The White Meat Controversymentioning
confidence: 77%
“…Interestingly, high calcium contents of experimental diets have been shown to reduce CRC risk associated with (processed) red meat intake both in animals (Sesink et al, 2001) and in humans , probably through interference with the effects of heme. In spite of the presence of inflammatory Neu5Gc, the significantly higher calcium levels in processed dairy products (»500 mg/100g) compared to processed red meat (»10 mg/ 100 g) (NUBEL, 2013) may thus account for the protective effects of dairy foods as reported earlier (Park et al, 2009;Pala et al, 2011). Anyway, the near absence of Neu5Gc in poultry and fish could provide an explanation for the "white meat controversy" and its importance justifies further research efforts.…”
Section: The White Meat Controversymentioning
confidence: 77%
“…1. We included eleven studies (11)(12)(13)(15)(16)(17)(18)(19)(35)(36)(37) that fully met our inclusion criteria for this meta-analysis. The characteristics of the included studies are summarised in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Their results became statistically non-significant after correcting for publication bias. The meta-analysis was followed by several subsequent prospective studies (15)(16)(17)(18)(19) that also focused on the same topic, but their findings continued to be inconsistent. To clarify the association between Ca intake and risk of breast cancer, we performed an updated meta-analysis of prospective studies.…”
mentioning
confidence: 99%
“…51 The 52 before including the study in the overall analysis. For studies that reported results for men and women separately, 33,40,43 and for studies that showed separate results for colon and rectal cancer, 35,49 we used fixed effect meta-analyses to obtain an overall estimate for overall gender and for colorectal cancer, respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…We included eight studies in "use-no use" meta-analysis, 34,37,40,[42][43][44][45][46] and six studies in "highest-lowest" meta-analysis. 34,37,40,[42][43][44] A statistically significantly decreased risk for colorectal cancer was observed in "useno use" ( Table 2, 2 5 0.0%, p 5 0.82) when we stratified for cancer site in "use-no use" metaanalysis, while heterogeneity was reduced for colorectal cancer (RR 5 0.91; 95% CI: 0.86,0.96), I 2 5 26.9%, p 5 0.21). "Dose-response" meta-analysis was based on six studies.…”
Section: Calcium Supplementsmentioning
confidence: 99%